La trame noire, un indicateur de la place de la nature dans l’aménagement du territoire - Magalie Franchomme; Christelle Hinnewinkel; Samuel Challéat (Bulletin de l’Association de Géographes Français)
The impact of artificial night lighting on the quality of the night sky, biodiversity and human health are now well known. The creation of a trame noire (set of practices to reduce light pollution), based on the model of the trame verte et bleue, may appear to be a relevant tool to meet the challenges of the energy and ecological transition. In recent years, many French municipalities have been experimenting with the modification of public lighting. However, the efficiency of these actions in environments impacted by artificial lighting sources may be raised. Through a strong partnership between research and public institutions, the TRAMENOIRE project studies the ecological and social challenges of setting up a night ecological network in the Lille European Metropolis (MEL). Based on a survey of MEL municipalities, we analyse the practices and motivations of public lighting stakeholders. These indirectly shed light on the process of social acceptability of such projects and the transition. Based on a survey of MEL municipalities, we analyse the practices and motivations of the municipalities. The survey indirectly sheds light on the process of social acceptability of such projects and the transition.